2021
DOI: 10.1136/bcr-2021-244146
|View full text |Cite
|
Sign up to set email alerts
|

Temporal association between SARS-CoV-2 and new-onset myasthenia gravis: is it causal or coincidental?

Abstract: Several case reports of COVID-19 in patients with myasthenia gravis (MG) have been documented. However, new-onset autoimmune MG following COVID-19 has been reported very rarely. We report one such case here. A 65-year-old man presented to us with dysphagia 6 weeks following mild COVID-19. He was evaluated and diagnosed as antiacetylcholine receptor antibody (AchR) positive, non-thymomatous, generalised MG. He subsequently developed myasthenic crisis and improved after treatment with intravenous immunoglobulin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“… 3 , 4 New onset myasthenia gravis associated with SARS CoV 2 infection has also been described. 5 - 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 , 4 New onset myasthenia gravis associated with SARS CoV 2 infection has also been described. 5 - 7 …”
Section: Discussionmentioning
confidence: 99%
“…The short time between vaccine administration and new diagnosis may also be explained by exacerbation of dormant or subclinical myasthenia gravis resulting in newly noticeable symptoms. 5 Subtle symptoms prior to vaccine administration may have been present but missed or ignored. Myasthenia gravis is underdiagnosed in those greater than 80 years old, with symptoms frequently misattributed to subjective fatigue and non-specific age-associated changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 was declared as a pandemic by WHO on March 11th, 2020. To date, accumulating evidence has confirmed that SARS-CoV-2 is linked to MG. 10 case reports of new-onset MG following COVID-19 have been analyzed with the following features: mean age 51 years, male gender (6), time interval between COVID-19 and MG (5-56 days), generalized (7), bulbar and/or ocular symptoms (5), anti-AChR antibodies (9) and anti-muscle specific kinase antibodies (anti-MUSK) (2) (93,94).…”
Section: Covid-19 Vaccines In Mg Patients Sars-cov-2 Infection and Mgmentioning
confidence: 99%
“…Variable conditions and neuropathies affecting the peripheral nervous system (PNS), including Guillain-Barrè syndrome and its variants ( 1 ), cranial multifocal neuropathy, dysautonomia ( 2 ), and brachial plexus lesion ( 3 ), have been described in subjects with COVID-19. Furthermore, neuromuscular disorders such as myalgia, myositis, and, in particular, myasthenia gravis (MG) have also been described ( 4 6 ). With regard to the association between MG and the COVID-19 infection, it has been observed that COVID-19 can exacerbate myasthenic crisis ( 7 ), promoting worsening of the clinical course and causing severe respiratory failure requiring intensive care unit (ICU) admission ( 8 ).…”
Section: Introductionmentioning
confidence: 99%